Indeterminate thyroid cytology: Detecting malignancy using analysis of nuclear images - Hayashi, Caroline Y. [UNESP]; Jaune, Danilo T A. [UNESP]; Oliveira, Cristiano C. [UNESP]; Coelho, Bárbara P. [UNESP]; Miot, Hélio A. [UNESP]; Marques, Mariângela E A. [UNESP]; Tagliarini, José Vicente [UNESP]; Castilho, Emanuel C. [UNESP]; Soares, Carlos S P. [UNESP]; Oliveira, Flávia R K. [UNESP]; Soares, Paula; Mazeto, Gláucia M F S. [UNESP] (Bioscientifica, 2021)
Background: Thyroid nodules diagnosed as 'atypia of undetermined significance/ follicular lesion of undetermined significance' (AUS/FLUS) or 'follicular neoplasm/ suspected follicular neoplasm' (FN/SFN), according to Bethesda’s classification, represena challenge in clinical practice. Computerized analysis of nuclear images (CANI) could be a useful tool for these cases. Our aim was to evaluate the ability of CANI to correctly classify AUS/FLUS and FN/SFN thyroid nodules for malignancy. Methods: We studied 101 nodules cytologically classified as AUS/FLUS (n = 68) or FN/SFN (n = 33) from 97 thyroidectomy patients. Slides with cytological material were submitted for manual selection and analysis of the follicular cell nuclei for morphometric and texture parameters using ImageJ software. The histologically benign and malignant lesions were compared for such parameters which were then evaluated for the capacity to predict malignancy using the classification and regression trees gini model. The intraclass coefficient of correlation was used to evaluate method reproducibility. Results: In AUS/FLUS nodule analysis, the benign and malignant nodules differed for entropy (P < 0.05), while the FN/SFN nodules differed for fractal analysis, coefficient of variation (CV) of roughness, and CV-entropy (P < 0.05). Considering the AUS/FLUS and FN/SFN nodules separately, it correctly classified 90.0 and 100.0% malignant nodules, with a correct global classification of 94.1 and 97%, respectively. We observed that reproducibility was substantially or nearly complete (0.61–0.93) in 10 of the 12 nuclear parameters evaluated. Conclusion: CANI demonstrated a high capacity for correctly classifying AUS/FLUS and FN/SFN thyroid nodules for malignancy. This could be a useful method to help increase diagnostic accuracy in the indeterminate thyroid cytology.
Keywords: Cell nucleus; Cytology; Diagnosis; Photography; Thyroid neoplasms